Interrater reliability of Thai version of the Structured Clinical Interview for DSM-IV Axis II Personality Disorders (T-SCID II) - Tinakon Wongpakaran (2018)
Objective: Explore the interrater reliability of Thai version of Structured Clinical Interview for DSM-IV Personality Disorders (T-SCID-II). Material and Method: Fifty-four psychiatric patients were assessed by seven psychiatrists. Each patient was interviewed independently and separately by two psychiatrists using T-SCID-II, with the second interview held within one to six weeks of the first. Results: The Kappa value between the first and second raters with regard to the diagnosis of each personality disorder, ranged from 0.70 for Depressive Personality Disorder, to 0.90 for Obsessive-compulsive Personality Disorder, with a mean of 0.81 for all the personality disorders. The mean trait intraclass correlation coefficient score was 0.90 and the summed score was 0.83. The overall interrater reliability was shown to be good across all the studies. Conclusion: Overall, Thai version of Structured Clinical Interview for DSM-IV Personality Disorders (T-SCID-II) showed between good and excellent reliability. Limitation of the present study and its generalizability was discussed.